Rare Mycotic Aneurysm of the Mitral Valve without Aortic Valve Involvement. Issue 9 (16th April 2015) - Zarrini, Parham; Elboudwarej, Omeed; Luthringer, Daniel; Siegel, Robert
<x xml:space="preserve">Abstract</x> Mycotic aneurysms can be a rare, but serious complication of infectious endocarditis. We report the case of a 20‐year‐old woman who presented with fever and malaise from streptococcal bacteremia and found to have vegetation on the anterior leaflet of the mitral valve. On follow‐up visit, the patient was noted to have a mycotic aneurysm of the anterior mitral valve without aortic involvement. Her clinical course was complicated by mitral valve chordal rupture, severe mitral regurgitation, and dyspnea from severe mitral regurgitation for which she underwent successful surgical repair of the mitral valve.